Sydney's guide to saving the planet - Ebono, Giovanni (Warriewood, N.S.W. : Woodslane Press, 2007)
A guide to environmental tips & advice for improving our environment.
"The future is not somewhere we are going, it is something we are creating" -- Professor Ian Lowe.
"With foreword by Professor Ian Lowe"--Cover.
"The Sydney Morning Herald"--Cover.
Includes index.
Keywords: Environmental protection -- New South Wales -- Sydney Region -- Citizen participation; Sydney Region (N.S.W.) -- Environmental conditions